2021
DOI: 10.7759/cureus.15590
|View full text |Cite
|
Sign up to set email alerts
|

The Young Heart Tears Easily Apart: A Case Report of Spontaneous Coronary Artery Dissection

Abstract: Spontaneous coronary artery dissection (SCAD) is a rare cause of acute coronary syndrome (ACS), seen mostly in young females. The rarity and limited knowledge of the disease make its management challenging. Prompt diagnosis of the condition is extremely important to decrease both long-and short-term complications. Treatment options depend on hemodynamic stability and the location of the dissection-with more distal lesions treated more conservatively as opposed to proximal lesions which are treated with percuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Coronary angiography is the first line of investigation with some limitations in precisely localizing the dissection entry point and identifying the true and false lumen. When coronary angiography can’t make the diagnosis, intracoronary imaging like IVUS and OCT can be used, as these imaging modalities give a more detailed analysis of the lesion [ 1 , 4 , 5 , 7 , 12 , 14 ]. However, intracoronary imaging may not be feasible in each case, particularly in those with severe tortuosity or when it involves more distal small-caliber arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronary angiography is the first line of investigation with some limitations in precisely localizing the dissection entry point and identifying the true and false lumen. When coronary angiography can’t make the diagnosis, intracoronary imaging like IVUS and OCT can be used, as these imaging modalities give a more detailed analysis of the lesion [ 1 , 4 , 5 , 7 , 12 , 14 ]. However, intracoronary imaging may not be feasible in each case, particularly in those with severe tortuosity or when it involves more distal small-caliber arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Stent placement or CABG is considered for patients with more proximal dissection, hemodynamic instability, dynamic ST-segment changes, and ventricular arrhythmias [ 4 , 12 ]. PCI is associated with the risk of dissection extension, guidewire passage into the false lumen, and major side branch restriction or blockade by hematoma [ 1 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first involves an intimal tear which results in blood collection in the intimal space from the endoluminal space forming false lumen which is termed as "inside-out". The second mechanism involves rupture of the vasa vasorum resulting in false lumen filled with hematoma which has also been referred to as "outside-in" [1,2]. Both these mechanisms lead to luminal encroachment and narrowing resulting in subsequent coronary artery obstruction causing myocardial ischemia and infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Other notable associated risk factors include systemic inflammatory disorders, multiparity, oral contraceptives, pregnancy, history of migraine, mechanical and emotional stressors [11]. Mechanical stressors including strenuous exercise have been classically associated with SCAD in males whereas emotional stressors are linked to SCAD in females [2]. A study conducted by Tweet et al reported that the incidence of pregnancy-related SCAD is more in multiparous women [12].…”
Section: Discussionmentioning
confidence: 99%
“…The outside-in mechanism, considered to be the most common form, suggests that the intramural hematoma forms within the vessel due to rupture of the vasa vasorum. The inside-out mechanism proposes the reverse in that the tear occurs first leading to a false lumen between the media and tunica intima [ 9 ].…”
Section: Discussionmentioning
confidence: 99%